Application of Chitosan Beads as the Bio-Adsorbent for Hexavalent Chromium Removal from Aqueous Solutions - Yuangsawad, Ratanaporn; ๋Jarenwongjongdee, Jirapat; Apiruksap, Benjarong (Frontiers in Engineering Innovation Research, 2022)
The adsorption of chromium hexavalent (Cr6+) from synthetic wastewater using sodium tripolyphosphate - crosslinked chitosan beads was investigated. The adsorption of Cr6+ on chitosan beads was carried out in a batch experiment. The effect of parameters on the Cr6+ removal such as pH, initial Cr6+ concentration, adsorption temperature and adsorbent dosage were studied. The results showed that the removal of Cr6+ increased continuously in the first 20 min of adsorption and reached the equilibrium within 90 min. The Cr6+ removal was strongly affected by pH and the adsorption was favored in acidic solutions. The highest Cr6+ removal was obtained at the pH value of 2.0, initial Cr6+ concentration of 2 mg/L and chitosan beads dosage of 2 g. The adsorption efficiency of Cr6+ was 92 and 86% for chitosan beads and chitosan powder, respectively. Additionally, the adsorption isotherms and kinetics of Cr6+ adsorption on chitosan beads were studied. The adsorption isotherm and kinetics data were well fitted to Langmuir model and pseudo second-order model, indicating that the adsorption of Cr6+ on chitosan beads is a single layer chemisorption. This study showed that chitosan beads could be considered as an efficient bio-adsorbent for Cr6+ removal and easily separated from aqueous solutions.